INSENTIF EKONOMI TERHADAP USAHA AQUACULTURE - Mira, Mira (Universitas Muhammdaiyah Surakarta, 2012)
The purpose of this study is to analyze the incentives for aquaculture businesses, one of these efforts is seaweed in Bone, South Sulawesi. Government intervention to develop the aquaculture business can be seen from the incentives provided. Incentives can be subsidized (at nursery) or in the form of protection (when the product is sold in the market). Incentives provided by the government in the form of policies, pay tax breaks or subsidies, have not touched this aquaculture business effectively. It can be seen from the value of the effectiveness of incentives for a commodity that is less than one (0.67). The government has not provided direct subsidies to farmers, unlike the fishing effort to get direct subsidies in the form of fuel prices (fuel oil) are relatively inexpensive for the fishermen. It can be seen from the value of subsidies for farmers who are negative (-0.3).